Маркетингове управління асортиментом продукції підприємства в умовах інформаційної економіки - Кузнецов, Павло Володимирович; Парфентенко, Ірина Анатоліївна; Балагула, Дар'я Петрівна (Український державний університет залізничного транспорту, 2015)
В роботі обґрунтовано теоретико-методичні положення та розроблено практичні рекомендації щодо маркетингового управління асортиментом продукції підприємства. Розглянуто сутність управління асортиментом та обґрунтовано необхідність цього процесу в умовах насиченості ринку харчової промисловості та жорсткої конкуренції. Визначено цілі маркетингового управління асортиментом, завдання, функції та методи. Розглянуто основні підходи щодо маркетингового управління асортиментом продукції підприємства відповідно до цілей його діяльності в умовах інформаційної економіки. В залежності від умов ринку, стану товарів та технологічного розвитку сформовано основні напрями діяльності підприємства.

In the work substantiated the theorist-methodical provisions and practical recommendations marketing management of assortment of products of the enterprise. First of all, highlighted the relevance of this process and the need in the current market conditions. Describes the main components of the marketing management of assortment of products. Defines the essence assortment management, as well as the role of marketing in the process of assortment management. Also in the work the the goals, objectives, functions and methods marketing management of assortment of products of the enterprise. Substantiates the necessity of this process in conditions of market saturation food industry and stiff competition. The basic approaches marketing management of assortment of products of the enterprise in accordance with the objectives of its activities. Depending on market conditions, the condition of the goods and technological development formed the main activities of the company. The strategy described marketing management of assortment of products, namely the strategy of diversification and concentration in the conditions of informative economy. Correctly chosen marketing strategy can help any business achieve its goals - to increase profits, develop new markets, etc. Conversely, incorrectly chosen strategy of development may adversely effect on the further activity the enterprise.
Marketing management of assortment of products of the enterprise
Keywords: асортимент; управління асортиментом; маркетингове управління асортиментом; товарна політика; планування асортименту; асортиментна політика; assortment; assortment management; marketing management assortment; assortment planning; assortment policy